Youtube to spread knowledge sharing in higher education - Gutiérrez Arenas, Mª del Pilar; De la Mata Agudo, Carmen; Álamo, Mercedes (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The use of social networks such as YouTube is becoming more and more common, and can favour collaborative learning and communication skills. That is why the research objective focused on finding out the opinion of university students on the results of their incorporation in the classroom. A sample of 97 students from two undergraduate degrees was used as the starting point for a mixed descriptive study. The results show that students are in favour of the use of this social network and believe that it facilitates the understanding of subject content.